2013
DOI: 10.1159/000346806
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Plasma Cell-Free Fetal and Maternal DNA at 11-13 Weeks' Gestation: Relation to Fetal and Maternal Characteristics and Pregnancy Outcomes

Abstract: Objective: To examine the possible relationship between maternal and fetal characteristics and pregnancy outcomes on fetal and maternal cell-free (cf) DNA in maternal plasma at 11-13 weeks' gestation. Methods: cfDNA was extracted from maternal plasma of 1,949 singleton pregnancies and chromosome-selective sequencing was used to determine the proportion of cfDNA and total cfDNA counts which was of fetal and maternal origin. Multivariate regression analysis was used to determine whether specific maternal and fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
2
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(124 citation statements)
references
References 40 publications
(57 reference statements)
10
101
2
9
Order By: Relevance
“…Although in our euploid group there was no significant association between fetal fraction and either maternal weight or serum-free β-hCG and PAPP-A, previous studies examining a higher number of pregnancies demonstrated a significant inverse association between fetal fraction and maternal weight and linear association between fetal fraction and both free β-hCG and PAPP-A [10,20,21,22]. The maternal blood level of fetal cfDNA decreases with increasing maternal weight due to a dilutional effect.…”
Section: Discussioncontrasting
confidence: 63%
“…Although in our euploid group there was no significant association between fetal fraction and either maternal weight or serum-free β-hCG and PAPP-A, previous studies examining a higher number of pregnancies demonstrated a significant inverse association between fetal fraction and maternal weight and linear association between fetal fraction and both free β-hCG and PAPP-A [10,20,21,22]. The maternal blood level of fetal cfDNA decreases with increasing maternal weight due to a dilutional effect.…”
Section: Discussioncontrasting
confidence: 63%
“…The third limitation of the test arises from the 1-5% rate of failure to provide results. An important cause of failure of cfDNA testing is low fetal fraction which is often a consequence of maternal obesity and this problem may be difficult to overcome [16,71,72,73]. Another potential disadvantage of cfDNA testing is the loss of useful information, beyond the detection of trisomies, which is derived from current methods of screening for trisomy 21 and invasive testing in the high-risk group [7].…”
Section: Discussionmentioning
confidence: 99%
“…The fetal DNA is significantly smaller than the maternal DNA in the bloodstream, with fragments with a median size of 146 bp and makes its way into the maternal bloodstream via shedding of the placental microparticles into the maternal bloodstream [23]. Fetal ccffDNA is heavily diluted with maternal plasma and this "fetal fraction" is positively correlated with gestational age while preliminary evidence suggests that it is negatively correlated with maternal weight [7,24,25]. In general, the fetal fraction percentage has to be provided and to be estimated with real-time quantitative PCR [22,26]: over 8% is considered satisfactory for most NIPT methods, while a 4-8% is considered marginal [11].…”
Section: Cell-free Dnamentioning
confidence: 99%
“…This is particularly important at early gestational ages, because the fetal fractions rise with increasing gestational age, and in women with high BMI, as fetal fractions are inversely proportional to weight [7,24,25]. To distinguish these minor differences with high confidence a large number of reads is required; because MPSS sequences all chromosomes, approximately 6.3 million uniquely-mapped reads from the entire genome are required to ensure sufficient, e.g., chromosome 21 counts for accurate copy number calls [27,[38][39][40].…”
Section: Ngs Nipt Approaches Quantitative Massively Parallel Shotgun mentioning
confidence: 99%